Ecotourism related search for information over the internet: a technology acceptance model perspective. Issue 1 (2nd January 2021) - Sadiq, Mohd; Adil, Mohd
ABSTRACT: The current study aims to understand as to how tourists use internet to search for information related to eco-tourism. Besides the mediating role of perceived usefulness, this study also attempts to determine the behavioural intentions and actual usage of tourists by extending the Technology Acceptance Model. A self-administered questionnaire in English was used to collect the data. The findings revealed that perceived ease of use, perceived usefulness, and electronic information quality significantly influence tourists' intentions to adopt technology which in turn influences their actual usage. The findings shed useful insights for the website/app developers on how they should provide a user-friendly interface along with credible information to influence tourists' behaviour.